Case Report: Ninjin'yoeito May Improve Quality of Life After Hospitalization for Acute Illness in Patients With Frailty - Kashima, Masayuki (Frontiers in Nutrition, 2021)
Introduction: Frail patients are susceptible to a large number of diseases, and frailty particularly is known to develop after acute illness. No conventional drugs are known to prevent such exacerbation after acute illness. However, traditional Japanese medicine, Kampo, is thought to confer efficacious energy and nutritional supplements and serve to improve malaise after acute illness. Ninjin'yoeito is a representative Kampo medicine for such situation. Cases: We describe three frail patients hospitalized for acute illness who started taking ninjin'yoeito at the time of discharge. Case 1: An 87-year-old man admitted with acute prostatitis complicated by hypertension and chronic obstructive pulmonary disease (COPD). His 36-Item Short Form Health Survey (SF-36) score, which is representative of total quality of life and comprises eight components, showed consistent improvements after 4 and 12 weeks of ninjin'yoeito administration, especially for body pain (BP; scores from 41 to 51 and 100, respectively), social function (SF; 50, 100, 100), and mental health (MH; 75, 75, 90). Case 2: A 65-year-old man admitted with urinary tract infection complicated by primary sclerosing cholangitis and COPD. All SF-36 component scores showed improvement 12 weeks later: physical function (PF; 70–95), role physical (RP; 75–100), BP (72–84), general health (GH; 45–52), vitality (VT; 37.5–75), SF 75–100, role emotional (RE; 75–100), and MH (70–90). Case 3: An 80-year-old man admitted for pneumonia complicated with hypertension. SF-36 score was improved 4 weeks later for RP (68.8–100), BP (52–61), GH (52–72), VT (43.8–62.5), SF (37.5–100), and RE (58.3–91.7). Conclusion: Patients with frailty often have a worsened SF-36 score after discharge following acute illness, but the score may be improved by taking ninjin'yoeito.